Women's political participation in Costa Rica: municipal elections 2020-2024 - Espinoza-Herrera, Rebeca (2024)
The objective of this article is to analyze the participation of women in decision-making positions in the Mayor's Offices and Deputy Mayor's Offices of local governments during the municipal elections of 2020 and 2024 in Costa Rica. This research is bibliographic and presents facts that accompany women's participation in the political sphere. It also addresses some of the main gender gaps, affirmative actions related to quotas, the principle of parity, alternation mechanisms, and the national and international regulatory framework concerning women's political rights. Additionally, an analysis of the statistics from the Supreme Electoral Tribunal of Costa Rica regarding the municipal elections of 2020 and 2024 was conducted. Among the main results, it is highlighted that although women's participation in mayoral positions increased in 2024 compared to 2020, participation remains unequal, and the principle of parity in candidacies has not yet been achieved. It is concluded that women's political participation is a fundamental human right that must be respected, protected, and guaranteed by the States.